Clinical characteristics and treatment modalities of vulvovaginal atrophy in genitourinary syndrome of menopause - Cho, Hae Jung; Seo, Jong Wook; Yoon, Ji Sun; Chung, Jae Eun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Genitourinary syndrome of menopause (GSM) causes symptoms such as vaginal dryness, dysuria, repetitive urinary tract infection and urinary urgency may affect daily activities, sexual relationships, and overall quality of life. The aim of the study was to provide the clinical characteristics of VVA patients in South Korea and the effectiveness as well as complications of the currently used low dose estrogen vaginal suppository. Methods: 52 women who has visited the outpatient gynecology clinic of the National Health Insurance Service Ilsan Hospital from January 2018 to December 2019 were recruited as study subjects. For the analysis of the clinical characteristics, subjective symptoms described by the patient’s own words such as vaginal dryness, pain, dysuria, dyspareunia, or no symptoms at all were included. Objective signs such as thinning of vaginal rugae, mucosal dryness, and mucosal fragility and the presence of petechiae were recorded. Results: Vaginal dryness was the most common complaint (92.3%). Thinning of the vaginal rugae was the most commonly noted objective sign (73.1%). Of the 52 subjects, 31 (59.6%) refrained from using the low dose estrogen vaginal suppository. The most common reason for not being able to use the suppository was the inability to insert the suppository (32.3%). Conclusions: Although patient-reported symptoms and clinical objectivity through physical examination are two components in diagnosing VVA, further study is warranted for a more objective and discriminatory diagnosis criteria for VVA. As the only available treatment modality was low dose vaginal estrogen suppository, comparison with other treatment modalities were not available.